Revenue distribution pattern and park-people conflict in Chitwan National Park, Nepal - Silwal, T; Shrestha, BP; Bhatta, BP; Devkota, BP (Banko Janakari, 2013)
This study has assessed patterns and consequences of park revenue sharing and implementation effectiveness to reduce park-people conflict in the Buffer Zone of Chitwan National Park. To explore programme implementation practice and consequences, two-thirds (n=14) of user committees were selected from the four management sectors. From the sampled committees, a questionnaire survey was randomly taken from user groups (n=100) to collect income and expenditure data. The revenue disbursement trends were favoured in community development works (roads, community buildings and schools) than conflict reduction issues. Fourty-two per cent of the total budget was allocated to infrastructures development, which was followed by conservation and conflict management (35%) and education (9%). Only a small amount of the budget was allocated to alternative energy, construction of animal preventive infrastructures to control wild-animals entering farmland and settlement, and provisions for wildlife damage compensation schemes. A certain part of the revenue should be allocated to wildlife victims. Furthermore, the process of providing relief funds should be shortened and simplified. Banko Janakari, Vol. 23, No. 1, Page 35-41 DOI: http://dx.doi.org/10.3126/banko.v23i1.9465